Subnational Population Estimates - Swanson, David A. author. aut Link
XIV, 414 p.
Keywords: Providing a unified and comprehensive treatment of the theory and techniques of sub-national population estimation, this much-needed publication does more than collate disparate source material. It examines hitherto unexplored methodological links between differing types of estimation from both the demographic and sample-survey traditions and is a self-contained primer that combines academic rigor with a wealth of real-world examples that are useful models for demographers. Between censuses, which are expensive, administratively complex, and thus infrequent, demographers and government officials must estimate population using either demographic modeling techniques or statistical surveys that sample a fraction of residents. These estimates play a central role in vital decisions that range from funding allocations and rate-setting to education, health and housing provision. They also provide important data to companies undertaking market research. However, mastering small-area and sub-national population estimation is complicated by scattered, incomplete and outdated academic sources—an issue this volume tackles head-on. Rapidly increasing population mobility is making inter-census estimation ever more important to strategic planners. This book will make the theory and techniques involved more accessible to anyone with an interest in developing or using population estimates. “With the publication of this volume, for the first time a book which is both a comprehensive and rigorous scholarly work as well as a user oriented and pragmatic methodological source has become available.” Steve Murdock, Rice University, Houston, TX, USA Steve Murdock, Rice University, Houston, TX, USA Steve Murdock, Rice University, Houston, TX, USA.